(untitled) (Modern education and development, 2024)
Childbirth due to premature rupture of membranes is often accompanied by abnormalities of labor, hypo- and atonic bleeding, high rates of trauma to the soft tissues of the birth canal, disruption of uteroplacental circulation and the development of fetal hypoxia.